Streptococcus mitis as a New Emerging Pathogen in Pediatric Age: Case Report and Systematic Review - Claudia Colomba; Valeria Garbo; Giovanni Boncori; Chiara Albano; Sara Bagarello; Anna Condemi; Salvatore Giordano; Laura A. Canduscio; Cristina Gallo; Gaspare Parrinello; Antonio Cascio (MDPI AG, 2023)
Streptococcus mitis, a normal inhabitant of the oral cavity, is a member of Viridans Group Streptococci (VGS). Generally recognized as a causative agent of invasive diseases in immunocompromised patients, S. mitis is considered to have low pathogenic potential in immunocompetent individuals. We present a rare case of sinusitis complicated by meningitis and cerebral sino-venous thrombosis (CSVT) caused by S. mitis in a previously healthy 12-year-old boy with poor oral health status. With the aim of understanding the real pathogenic role of this microorganism, an extensive review of the literature about invasive diseases due to S. mitis in pediatric patients was performed. Our data define the critical role of this microorganism in invasive infections, especially in immunocompetent children and in the presence of apparently harmful conditions such as sinusitis and caries. Attention should be paid to the choice of therapy because of VGS's emerging antimicrobial resistance patterns.